Bahasa Indonesia Bahasa Indonesia - Kustiyono Kustiyono; Daniel Manongga (Postgraduate, University of Mataram, 2023)
In these lately years, teamwork already got considered to be matters more for every kind of organization. Working in teams helps people to be more flexible, productive, and creative than working alone, as well as to keep their jobs and be happier at work. This research was done on purpose to help defining the influence of digital literacy, technology support, and virtual team leadership toward virtual team collaboration in tertiary institutions in influencing the way virtual teams work together. In this study, the questionnaire used a Google Form, which was sent via email to the appropriate email address. The findings reveal that the three antecedent variables significantly influence virtual cooperation by 62.3%. This research theoretically has offered a virtual collaboration model that has been evaluated empirically in the field. In addition, this model has enlarged the elements that influence virtual team collaboration from several previous studies. The findings of this study apply to administrators in tertiary institutions who seek to increase collaboration between lecturers, especially in the fields of teaching, research, and publication. In this context, the antecedents of this virtual collaboration model can be considered